PENGUASAAN NEGARA DAN PERAN MASYARAKAT ATAS SEKTOR PERTAMBANGAN MINERAL DAN BATUBARA - Szyva Silviana Putri (PENERBIT LAFADZ JAYA, 2022)
Indonesia has a lot of natural resources, one of which is minerals and coal. Of course, in its management must be with the attention and role of the government in the management of these resources. The role of the government in mastery in the mining sector is needed. What's more, the mining sector is a sector that is in great demand by foreign investors, so the government must take part in regulators to regulate exploitation in the mining sector. so that the creation of balance in its use or management which of course must be based on the welfare of the people. Therefore, the guidelines for the rule of law in the management of minerals and coal are needed in their application. So that in carrying out and managing it in accordance with the NRI Constitution, as well as the applicable law in order to get maximum utilization of natural resources without damaging nature, so that posterity can feel and utilize it as well